2014
DOI: 10.1177/1533034614561359
|View full text |Cite
|
Sign up to set email alerts
|

Association Between WRN Cys1367Arg (T>C) and Cancer Risk

Abstract: Growing evidence suggests that aberration of the DNA repair pathway significantly contributes to tumorigenesis. Singlenucleotide polymorphisms in DNA repair-related genes such as WRN have been implicated in cancer risk. However, the results of published studies remain inconclusive. Therefore, we performed a meta-analysis of all available and relevant published studies to clarify the role of this polymorphism in cancer. We performed a computerized search of PubMed for publications on WRN Cys1367Arg (T>C) polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…In our study p.V114L was not associated with total cancer, but only nominally associated with adenocarcinoma, which is likely a spurious association (data not shown). p.C1367R has also been shown to associate with various cancers [14][15][16][17][18], but we did not find any sign of association with total cancer presence in our cohort.…”
Section: Genotyping and Statistical Analysiscontrasting
confidence: 94%
“…In our study p.V114L was not associated with total cancer, but only nominally associated with adenocarcinoma, which is likely a spurious association (data not shown). p.C1367R has also been shown to associate with various cancers [14][15][16][17][18], but we did not find any sign of association with total cancer presence in our cohort.…”
Section: Genotyping and Statistical Analysiscontrasting
confidence: 94%
“…27 In addition, a meta-analysis evaluated 7 epidemiologic studies and demonstrated that the CC genotype of Cys1367Arg polymorphism was also associated with a 1.43-times increased risk of breast cancer. 25 A case-control study in Chinese women that included approximately 4000 patients also showed that the variant genotype of WRN Leu1074Phe was associated with a 1.36-times higher risk of breast cancer. 26 We have previously shown, at a transcriptomic level, that low WRN mRNA expression was associated with aggressive clinicopathologic features such as high grade, lymph node stage, and human epidermal growth factor receptor 2 (HER2) overexpression and distinct aggressive molecular phenotypes as described by Curtis et al, 28 including PAM50.Her2, PAM50.LumB, Genufu subtype (ER þ /HER2 À /high proliferation), and Genufu subtype (HER2 þ ) breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Genetic epidemiologic studies identified certain polymorphisms of the WRN gene that are associated with increased risk of breast cancer. [25][26][27] Specifically, the CC genotype of WRN rs1346044 has been associated with a 2-fold risk of developing breast cancer. 27 In addition, a meta-analysis evaluated 7 epidemiologic studies and demonstrated that the CC genotype of Cys1367Arg polymorphism was also associated with a 1.43-times increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%